A flexible microporous framework with temperature-dependent gate-opening behaviours for C2 gases. Issue 31 (18th March 2021) - Ji, Zhenyu; Fan, Yerong; Wu, Mingyan; Hong, Maochun
Abstract : A flexible framework has uncommon temperature-dependent gate-opening behaviors for C2 gases around room temperature. Abstract : Herein we report a two-fold interpenetrating pillar-layer microporous material, whose framework severely shrinks after losing guest molecules and transforms into a stable nonporous one. More importantly, the guest-free framework has rarely seen temperature-dependent gate-opening behaviours for C2 gases around room temperature.